The Role of Exogenously Applied Polyamines to Improve Heat Tolerance in Tomatoes: A Review - Raheleh Najafi; Noémi Kappel; Maryam Mozafarian (Agriculture)
Tomato (Solanum lycopersicum L.) is one of the most widely consumed vegetables globally and plays a crucial role in food security. However, rising temperatures due to climate change pose a significant threat to tomato cultivation by reducing yield and fruit quality. Among various abiotic stresses, heat stress (HS) can severely impair tomato growth, reproduction, and physiological functions. Polyamines (PAs), such as spermidine (Spd), putrescine (Put), and spermine (Spm), are natural compounds that play vital roles in plant stress tolerance by modulating growth and physiological responses. This review evaluates the effects of HS on tomatoes and examines the potential of exogenously applied PAs to mitigate HS. Through detailed analysis of agronomic, physiological, and biochemical responses, the review highlights how PAs can enhance heat tolerance by improving antioxidant activity, stabilizing cellular membranes, and maintaining photosynthetic efficiency. Understanding these mechanisms can aid in developing strategies to improve tomato resilience under climate stress and ensure sustainable production.